Creative Innovation of Multifunctional Painted Shawl - Nisa, Apriliana Putri Khairun; Pemayun, Tjokorda Udiana Nindhia; Budiaprilliana, Luh (Program Studi Seni Murni ISI Bali, 2023)
Multifunctional Painting Shawl is a product of 4moon that emphasizes Functional and beauty. According to Wikipedia, Shawls is a traditional Indonesian clothing in the form of a long cloth. Shawls are usually used by women. This shawl is specially designed to have several functions at once in one object only. Not only functional, the 4moon shawl also has additional aesthetic value found in the surface design and additional prada. The purpose of this study are 1) To find out the Transfer of Knowledge of Multifunctional Painting Shawl Entrepreneurial Governance, 2) To find out the Transfer of Multifunctional Painting Shawl Entrepreneurial Skills, 3) To find out the Transfer of Knowledge and Marketing Technology of multifunctional Painting Shawl, 4) To find out the Analysis of multifunctional Painting Shawl Entrepreneurship activities. This type of research is included in quantitative research and observation as a method of data collection. The result of the study are 1) There are 6 multifunctional painting shawl products by 4moon 3) Marketing that the author does is offline and online such as Instagram. The author also applies a custom-order system 4) Adding insights such as adding prada using massage canting techniques